SMALL-ANGLE SCATTERING OF NEUTRONS ON Sr2FeMoO6–δ SAMPLES WITH DIFFERENT-DEGREE SUPERSTRUCTURAL ORDERING OF Fe/Mo CATIONS - L. I. Hurski; N. A. Kalanda; M. V. Yarmolich; I. A. Bobrikov; A. L. Zhaludkevich; P. N. Kireev; D. A. Krivchenya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
Single-phase Sr2FeMoO6-δ samples with different-degreesuperstructiral ordering Fe/Mo cations superstructural ordering (P, 76, 86 and 93 %) were obtained by the solid-phase technique. Based on the results of measuring the magnetic characteristics in the samples, we found that an increase in magnetization (26.41, 32.36 and 42.66 A·m2·kg–1), magnetic moment (1.33, 3.07 and 3.58 μB/f.u.) and Curie temperatures (422, 428 and 437 K) withparameter P (76, 86 and 93 %) can be explained by the presence of antistructural defects, as well as antiferromagnetic inclusions. This determines the redistribution of electron density, which is accompanied by the change in electronic configuration of a part of Fe/Mo cations. Based on the temperature dependences of the magnetic moment of the samples measured in ZFC and FC modes, and on small-angle polarized neutron scattering (SANS), we found that the samples are in a magnetically inhomogeneous state. An important result to mention is that we detected the difference between the slope of the SANS curves of samples with different oxygen content, which demonstrates a different microstructure of inhomogeneities. The main inhomogeneities are magnetic inclusions with the dimensions depending on the superstructural ordering of Fe/Mo cations. According to the Porod law, it was shown that the Sr2FeMoO6-δ samples with wave vector values 0.1 > q > 0.002 Å–1 contain polydisperse grains with a smooth surface. For q > 0.1 Å–1 a deviation from the Porod law is observed, confirming the presence of magnetic inhomogeneities with a diameter < 6 nm in the grains.